PERSPEKTIF ISLAM TERHADAP PENDIDIKAN MULTIKULTURAL DALAM KONTEKS SEKOLAH DASAR - Pane, Derliana; Fata, Nahriyah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This article examines and describes through a literature study on Islamic perspectives on multicultural education in the context of elementary schools. Multicultural education is very important for many people, elementary schools have a very important role in the foundation of education in instilling the values of tolerance, mutual respect, and diversity. On this basis, this article analyzes Islamic principles such as rahmatan lil 'alamin, justice, equality, and respect for differences as a normative foundation in supporting multicultural educational practices. The article also reviews some of the literature that links Islamic teachings to inclusive and humanist pedagogical approaches in primary school settings. The results of the study show that Islamic values are essentially in line with the principles of multicultural education, resulting in the integration of both to strengthen the formation of students' character in dealing with socio-cultural diversity in a positive and constructive manner. This article is expected to be used as a reference for the development of curriculum and learning practices oriented to multicultural values based on Islam.